Relationship between Commercial Banks of Thailand Services Quality and Performance - ยักกะพันธ์, ดารากร; วีรยางกูร, มนตรี; ภูมิบ่อพลับ, วรพงศ์ (Journal of Management Sciences Suratthani Rajabhat University, 2017)
The purpose of the research were to study the relationship between variables affecting functional service quality and the Commercial Thai Banks’ performance. Specific factors influencing the technical service quality of the Commercial Banks of Thailand and variables influence of the factors influencing through the service quality of the Commercial Banks of Thailand were analyzed using data questionnaires. Samples were collected using specific methods from the top five ranked with the best performance and the largest number of branches.After that we used the exact demographic formula of Yamane have 381 branches.The responses were at 52 %, using the AMOS program to analyze the modeling of Structural Equation. Results revealed that the modeling equivalence was consistent with the empirical data which indicated that the Structural Equation Modeling and the Performance of the Commercial Banks of Thailand was consistent with the empirical data in the condition following of the statistical significance. Our results concluded that the relevant variables between the service quality and the performance of the commercial banks of Thailand consisted of working service, technical service quality, service quality, which all affected the performance of Commercial Banks in Thailand. Work service quality most directly direct affected to the Banks’ performance. Variables influencing technical service quality were direct and indirect service quality, and involved the relationship between the service quality and the performance of the Commercial Banks of Thailand. The Service quality variable most positivelyinfluenced the performance of the Commercial Banks of Thailand, and technical service quality variable had the highest influence on both the service quality and the performance of the Commercial Banks in Thailand. In contrast, the working service quality affected both the service quality and the performance of the Commercial Banks in Thailand respectively. The results are consistent with Mamoun N. AkroushFahed S. Khatib (2009). They studied the impact of service quality dimensions on performance in an empirical investigation of Jordan’s commercial banks. Their research findings indicated that service the service quality dimensions (functional and technical) both positively and significantly affected banks performance, and assessments based on financial performance and customer indicators are consistent with this research.